Penerapan Pembelajaran Aktif Berbasis Tugas Proyek untuk Meningkatkan Hasil Belajar IPA Siswa Kelas VII B SMP Kristen 2 Salatiga Tahun Pelajaran 2016/2017 Active Learning Application Based on Project Assignment in Improving Science Learning Results of Stu - Kurniawan, Muhammad Kharis; Keliat, Natalia Rosa; Krave, Agna S.; Hutagaol, Daud Ronal (Bioedukasi: Jurnal Pendidikan Biologi, 2017)
ABSTRACT                 The purpose of this study is to find out the active learning application based on project assignment in improving science learning results of students in VII B class of SMP Kristen 2 Salatiga and to find out the improvement of the science learning results of students in VII B class of SMP Kristen 2 Salatiga throuh applying the active learning based on the project assignment. This study was done in SMP Kristen 2 Salatiga by using 21 students in this school as the subjects. The method applied in this study is the descriptive analysis method with the data collection instruments such as questionnaires, pbservation sheets and interview. The results of this study show that the active learning model based on the project assignment could improve students’ cognitive, psychomotor and affective learning results. Based on the students’ cognitive learning results, the students’ percentage fulfilling the minimum criteria (KKM) in cycle 1 is 66.67% and it improves into 90.47% in cycle 2. Based on the students’ psychomotor learning results, the students’ percentage fulfilling the minimum criteria (KKM) with a good criterion (≥ 25) in cycle 1 is 76.19% and it improves into 100% in cycle 2. Based on the students’ affective learning results, the students’ percentage fulfilling the minimum criteria (KKM) with a good criterion (≥ 25) in cycle 1 is 80.95% and it improves into 100% in cycle 2.Keywords : Active Learning Based on Project Assignment, Learning Results